2016
DOI: 10.1111/roie.12228
|View full text |Cite
|
Sign up to set email alerts
|

Does Real Estate Defy Gravity? An Analysis of Foreign Real Estate Investment Flows

Abstract: This paper investigates the scale and determinants of foreign investment flows between national real estate markets. Using data for over 100 countries over 2007-2012, the results indicate that, consistent with previous studies for trade, foreign direct and portfolio investment variables such as size and distance have significant effects on foreign real estate investment flows. Large positive size effects are consistent with a combination of scale economies and information externalities producing investment con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
(61 reference statements)
1
19
0
Order By: Relevance
“…In a similar vein, Hoyler et al (2014) in an examination of the relationship between international real estate investment flows and city connectivity found that global cities with high financial and APS connectivity have high international real estate capital inflows, implying the concentration of international office investments in global cities. Indeed, Hoyler et al (2014) suggested that international real estate investment inflow is a proxy for global financial networks and numerous studies (Lizieri and Pain, 2014; Stevenson et al , 2014; McAllister and Nanda, 2016) have explored the consequences of such capital flow concentration within global cities. Pertinently, Lizieri and Pain (2014) argued that such concentration whilst increasing returns performance also enhances exposure to international financial market risk.…”
Section: Literature Review: Capital Market Flowsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, Hoyler et al (2014) in an examination of the relationship between international real estate investment flows and city connectivity found that global cities with high financial and APS connectivity have high international real estate capital inflows, implying the concentration of international office investments in global cities. Indeed, Hoyler et al (2014) suggested that international real estate investment inflow is a proxy for global financial networks and numerous studies (Lizieri and Pain, 2014; Stevenson et al , 2014; McAllister and Nanda, 2016) have explored the consequences of such capital flow concentration within global cities. Pertinently, Lizieri and Pain (2014) argued that such concentration whilst increasing returns performance also enhances exposure to international financial market risk.…”
Section: Literature Review: Capital Market Flowsmentioning
confidence: 99%
“…Pertinently, Lizieri and Pain (2014) argued that such concentration whilst increasing returns performance also enhances exposure to international financial market risk. In advancing these arguments, McAllister and Nanda (2016) contended that the concentration of foreign investments leads to yield compression in the office sector due to the increase in the intensity of competition for limited suitable products. Concomitantly, Hoyler et al (2014) illustrated that global cities are often considered “safe havens” for investors, as demonstrated by the “flight to prime” during and after the GFC, principally due to the transparency, intrinsic value and liquidity within these cities.…”
Section: Literature Review: Capital Market Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies identify distance as a key explanatory variable for price, especially in the case of purchasers. Distance contains a number of institutional, cultural and informational factors that can increase information asymmetry, search costs and other costs, potentially putting the non-local investor at a disadvantage (see McAllister and Nanda 2016a). However, the relationships between investor proximity and pricing might not be the same when it comes to domestic versus foreign investors, while evidence of a price premium for foreign investors would not necessarily provide proof of over-payment for assets because they may possess cost-of-capital advantages or be paying for added diversification benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the behaviour and impact of foreign investors in commercial real estate markets has increased in the academic literature. Recently, Lieser and Groh (2014) and McAllister and Nanda (2016a) have analysed determinants of cross-border capital flows, while Mauck and Price (2015) have looked at the determinants of foreign ownership at the asset level. Nanda (2015, 2016b) tested whether an increased presence of foreign investors causes capitalization rates in a city to be lower, all else equal.…”
Section: Introductionmentioning
confidence: 99%